The Role, Management, and Fragility of Trust within Strategic Enterprises in Multi-national Enterprises - Thum, Sven Roman (2011)
Over the last two decades, the globalisation of markets has resulted in multi-national enterprises to focus on their core competencies and outsource their sub-process to partners that were specialised in that particular area. That in turn has led to the realisation for close collaboration with partners on critical processes and the formation of strategic partnerships. A key ingredient for successful strategic partnerships is trust. This paper looks at the issue of trust from buyer perspective and first deals with a review of literature regarding the role of trust, factors leading to trust creation and development, as well as the fragility of trust. Second, based on the literature, three research gaps comprising (A) the role of interpersonal and interorganisational trust, (B) the process of trust creation and development, as well as (C) the fragility of trust and successive the process of trust erosion were identified. In a second step, this paper tries to fill this research gap by analysing empirical data from a case study research involving Airbus S.A.S. and some of its strategic partners, such as Rolls-Royce, General Electric. Thereby, the analysis was based on data from key management personnel at Airbus S.A.S. and consultants involved in some cases. The findings suggest that both interpersonal and interorganisational trust is important, however, this is sensitive to cultural values. In addition, the process of trust creation and development involves a modest approach to suppliers combined with a cultivation of personal contacts. Finally, trust has been found more robust than expected and the process of trust erosion involves a loss of interorganisational trust at first and is followed by a loss of interorganisational trust.